2015
DOI: 10.2196/mhealth.3789
|View full text |Cite
|
Sign up to set email alerts
|

Patient Engagement With a Mobile Web-Based Telemonitoring System for Heart Failure Self-Management: A Pilot Study

Abstract: BackgroundIntensive remote monitoring programs for congestive heart failure have been successful in reducing costly readmissions, but may not be appropriate for all patients. There is an opportunity to leverage the increasing accessibility of mobile technologies and consumer-facing digital devices to empower patients in monitoring their own health outside of the hospital setting. The iGetBetter system, a secure Web- and telephone-based heart failure remote monitoring program, which leverages mobile technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 19 publications
(20 reference statements)
2
97
2
2
Order By: Relevance
“…Only three of the studies reported the racial composition of their study sample (overall, 68% White, 18% Black, 14% other race) and all were conducted in North America. 2224 The remaining 6 studies were conducted in Europe and Australia. Study duration ranged from 4 weeks to 24 months.…”
Section: Resultsmentioning
confidence: 99%
“…Only three of the studies reported the racial composition of their study sample (overall, 68% White, 18% Black, 14% other race) and all were conducted in North America. 2224 The remaining 6 studies were conducted in Europe and Australia. Study duration ranged from 4 weeks to 24 months.…”
Section: Resultsmentioning
confidence: 99%
“…This study included taking daily weight and blood pressure readings, weekly single-lead ECGs, and daily symptom questions on a mobile phone over 6 months with feedback both to the patient and the cardiology provider (Table 1). A more recent example is the remote monitoring system called iGetBetter [15] (Partners, Boston), which enables patients to self-monitor by being able to take their weight using a Bluetooth scale, blood pressure, and heart rate measurements. Patients can view their results on an iPad mini tablet computer (Apple Inc, Cupertino, CA, USA) equipped with cellular internet connectivity [15].…”
Section: Potential Applications Of Gerontechnologies For Older Adultsmentioning
confidence: 99%
“…This can be challenging because symptom changes can be so insidious that patients have difficulty recognizing and responding to them, as well as differentiating them from symptoms of other chronic conditions including, depression [11], atrial fibrillation, diabetes, and chronic kidney disease [12]. Despite these difficulties, active participation in self-care management is crucial in heart failure because patients who are involved in their own care are more likely to have improved survival, decreased readmission rates, and better quality of life [1315]. …”
Section: Introductionmentioning
confidence: 99%
“…All clinical stakeholders can benefit. Early work has highlighted potential uses, such as low-resource remote monitoring of congestive heart failure patients obtaining weight, blood pressure, and heart rate [24]. Pharmaceutical companies have already begun integrating the use of technology to incorporate PROMs into clinical trials.…”
Section: Digital Outcome Measuresmentioning
confidence: 99%